Kolose 3:18 - 4:1 Sebagai Jawaban Terhadap Hegemoni Maskulinitas Kepala Keluarga - Paulus Dimas Prabowo; Arman Susilo; Jessi Darius (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
The Colossian congregation lived in a Greco-Roman household culture that was thick with the hegemonic masculinity of the head of the family, so that wives, children and slaves experienced arbitrary treatment. Christianity certainly does not allow this kind of thing to happen in Christian households. This article attempts to prove that Colossians 3:18 – 4:1 was used by Paul to deal with hegemonic masculinity at that time. The method used is epistolary genre hermeneutics. A study of Colossians 3:18 – 4:1 by paying attention to structure, grammar, and cultural context shows that Paul uses an inferior-superior formula in the structure of household rules, gives new values to the roles of each member, and bases all actions on the superiority of Christ. Paul still respected the existence of the existing social hierarchy but modified it in terms of values and practices.